Food Prices: Eastern and Southern Africa Defy Global Trends - Macharia, E.; Gbegbelegbe, Sika; Wanjiku, J.; Karugia, Joseph T. (International Food Policy Research Institute, 2009)
Global food prices started rising sharply in 2006 and reached record levels in the second quarter of 2008. Although domestic food prices in Eastern and Southern Africa (ESA) are not totally unrelated to world prices, a study by the Association for Strengthening Agricultural Research in East and Central Africa (ASARECA), the Regional Strategic and Knowledge Support System for Eastern and Central Africa (ReSAKSS-ECA), and the Consultative Group on International Agricultural Research (CGIAR) Alliance shows that national and regional factors are very important in driving domestic food prices. While global food prices have exhibited declining trends since June 2008, several ESA countries have experienced increasing prices in 2008 and early 2009. The price surges appear to be further fuelled by some of the policy responses that countries have employed in their attempts to address the food price problem. This brief provides an update on food price trends in ESA. It starts by comparing the Food and Agricultural Organization of the United Nations (FAO) global food price index and food price indexes (FPI) in individual countries followed by an update on price trends for specifi c commodities. This information serves to remind policymakers that the easing global food prices do not present any immediate relief to the food crises facing their individual countries.